Graphene oxide as an active carbocatalyst for cyanation of quinoline and isoquinoline N-Oxides. (12th March 2021) - Huang, Panpan; Peng, Xiangjun; Qiu, Genhong; Yu, Keyang; Li, Hong; Kong, Lingting; Hu, Jiaming; Chen, Zhengwang; Huang, Qing; Liu, Liangxian
Abstract: Graphene oxide was found to be a highly efficient and cost-effective heterogeneous catalyst for the direct metal-free transformation of quinoline and isoquinoline N -oxides into the corresponding nitriles under mild conditions. This method is simple, economic and environmentally benign, representing a useful strategy for the convenient synthesis of α-cyano N -oxides that are difficult to prepare by transition-metal-free catalyzed methods. In vitro, compound 2s exhibited good activities against T-24 cell lines with IC50 values in 10.23 ± 1.05 μM. Further studies investigated the mechanism of the effective inhibition of cell growth, including apoptosis ratio dection, cell cycle analysis, measurement of Ca 2+ generation, ROS, and mitochondrial dysfunction. Graphical abstract: Image 1 Highlights: The GO-catalyzed cyanation of N -oxides under metal-free and base-free reaction conditions. This protocol is green and practical due to the use of inexpensive GO as the catalyst. 4-Bromo-1-cyanoisoquinoline 2-oxide exhibited good activities against T-24 cell lines. This protocol is not accompanied by the N-O bond cleavage.